Izzivi in ukrepi zavarovanih območij na področju mobilnosti v Sloveniji - Goluža, Maruša (Geografski obzornik, 2025)
Protected areas in Slovenia face increasing traffic pressure, threatening natural values and the quality of life of local communities. To date, a comprehensive review of the challenges and measures in Slovenian protected areas in the field of mobility has not been conducted. A review of management plans and online stakeholder survey results shows that many challenges cannot be solved independently. Effective sustainable mobility planning requires cooperation among municipalities, protected area managers, and state institutions. This paper presents a conceptual and practical framework for traffic management.
Keywords: accessibility; active mobility; governance; javni potniški promet; prometna dostopnost; public transport; Slovenija; sustainable mobility; trajnostna mobilnost; trajnostni turizem; upravljanje; zavarovana območja